The potential for improving cardio-renal outcomes in chronic kidney disease with the aldosterone synthase inhibitor vicadrostat (BI 690517): a rationale for the EASi-KIDNEY trial - Judge, Parminder K.; Tuttle, Katherine R; Staplin, Natalie; Hauske, Sibylle J.; Zhu, Doreen; Sardell, Rebecca; Cronin, Lisa; Green, Jennifer B; Agrawal, Nikita; Arimoto, Ryoki; Mayne, Kaitlin J; Sammons, Emily; et al. (Nephrology, dialysis, transplantation, 2025)
Patients with chronic kidney disease (CKD) are at risk of progressive loss of kidney function, heart failure, and cardiovascular death despite current proven therapies, including renin-angiotensin system inhibitors (RASi), sodium glucose co-transporter-2 inhibitors (SGLT2i), and statin-based regimens. RASi and SGLT2i reduce risk of CKD progression irrespective of primary cause of kidney disease, suggesting they target final common pathways. Targeting aldosterone overactivity with a nonsteroidal mineralocorticoid receptor antagonist (MRA) also reduces cardiorenal risk in patients with albuminuric diabetic kidney disease already treated with RASi. Together, these observations provide the rationale for trials to assess effects of inhibiting the aldosterone pathway in a broader range of patients with CKD, including those with non-diabetic causes of CKD or low albuminuria. Aldosterone synthase inhibitors (ASi) have emerged as an alternative to MRAs for aldosterone pathway inhibition. Phase II data from 586 patients with albuminuric CKD have shown that 10 mg of an ASi, vicadrostat (BI 690517), reduced urine albumin-to-creatinine ratio by ∼40% compared with placebo, with or without concurrent empagliflozin treatment. MRA and ASi increase risk of hyperkalaemia. Combining their use with an SGLT2i may mitigate some of this risk, improving tolerability, and allowing a wider range of patients to be treated (including those with higher levels of blood potassium than in previous trials). The EASi-KIDNEY (NCT06531824) double-blind placebo-controlled trial will test this approach by assessing the safety and cardiorenal efficacy of vicadrostat in combination with empagliflozin in ∼11 000 patients with CKD. It will be sufficiently large to assess effects in patients with and without diabetes separately.